Preparing entangled states between two NV centers via the damping of nanomechanical resonators. Issue 1 (December 2017) - Li, Xiao-Xiao; Li, Peng-Bo; Ma, Sheng-Li; Li, Fu-Li
Abstract We propose an efficient scheme for preparing entangled states between two separated nitrogen-vacancy (NV) centers in a spin-mechanical system via a dissipative quantum dynamical process. The proposal actively exploits the nanomechanical resonator (NAMR) damping to drive the NV centers to the target state through a quantum reservoir engineering approach. The distinct features of the present work are that we turn the detrimental source of noise into a resource and only need high-frequency low-Q mechanical resonators, which make our scheme more simple and feasible in experimental implementation. This protocol may have interesting applications in quantum information processing with spin-mechanical systems.